Analisis Human Error Guna Meminimalkan Kecelakaan Kerja Dengan Menggunakan Metode SHERPA dan HEART - Muhammad Rifqi Al Ma’aarij; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
A safe and comfortable company is an organized and well-maintained company that is able to guarantee the safety and health of workers in carrying out their work. The more facilities that support work safety are available, the smaller the chance of a work accident. This study aims to determine how to minimize human error that occurs in CV. Technical Prosperity Facilities. The research method uses the Systematic Human Error Reduction and Prediction Approach (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods. The method of data collection is done by interviewing directly with the owner of the company. The type of data used is qualitative data. From the results of the analysis, it can be concluded that the application of K3 at CV Sarana Sejahtera Tehnik is still not optimal so that K3 facilities can be improved at the company, and carry out work evaluations.